Enhancement of immune response towards non-lipidized Borrelia burgdorferi recombinant OspC antigen by binding onto the surface of metallochelating nanoliposomes with entrapped lipophilic derivatives of norAbuMDP - Křupka, Michal; Mašek, Josef; Bartheldyová, Eliška; Turánek Knötigová, Pavlína; Plocková, Jana; Korvasová, Zina; Škrabalová, Michaela; Koudelka, Štěpán; Kulich, Pavel; Zachová, Kateřina; Czerneková, Lýdie; Strouhal, Ondřej; et al. (Journal of controlled release, 2012)
Lyme disease caused by spirochete Borrelia burgdorferi sensu lato, is a tick-born illness. If the infection is not eliminated by the host immune system and/or antibiotics, it may further disseminate and cause severe chronic complications. The immune response to Borrelia is mediated by phagocytic cells and by Borrelia-specific complement-activating antibodies associated with Th1 cell activation. A new experimental vaccine was constructed using non-lipidized form of recombinant B. burgdorferi s.s. OspC protein was anchored by metallochelating bond onto the surface of nanoliposomes containing novel nonpyrogenic lipophilized norAbuMDP analogues denoted MT05 and MT06. After i.d. immunization, the experimental vaccines surpassed Alum with respect to OspC-specific titers of IgG2a, IgG2b isotypes when MT06 was used and IgG3, IgM isotypes when MT05 was used. Both adjuvants exerted a high adjuvant effect comparable or better than MDP and proved themselves as nonpyrogenic.
Keywords: protilátky bakteriální; Animals; Microscopy, Electron, Transmission; Electrophoresis, Polyacrylamide Gel; Enzyme-Linked Immunosorbent Assay; Female; Borrelia burgdorferi; antigeny bakteriální; Calorimetry, Differential Scanning; Spectrometry, Mass, Matrix-Assisted Laser Desorption-Ionization; proteiny vnější bakteriální membrány; ženské pohlaví; Nanoparticles; Liposomes; Drug Carriers; Bacterial Outer Membrane Proteins; Lyme Disease Vaccines; Mice; diferenciální skenovací kalorimetrie; Mice, Inbred BALB C; nanočástice; liposomy; myši; Antibodies, Bacterial; Light; Acetylmuramyl-Alanyl-Isoglutamine; ELISA; myši inbrední BALB C; chelátory; vakcína proti lymeské nemoci; acetylmuramyl-alanyl-isoglutamin; Antigens, Bacterial; Chelating Agents; nosiče léků; radiační rozptyl; spektrometrie hmotnostní - ionizace laserem za účasti matrice; transmisní elektronová mikroskopie; zvířata; světlo; elektroforéza v polyakrylamidovém gelu; Scattering, Radiation